Interaction of Aromatic Nitro Compounds and Fluoride Ions with Photoluminescent GO‐Ce Nanoparticles: Understanding the Role of Local Environment of Cerium. Issue 35 (13th September 2022) - Pyne, Dinesh K.; Pramanik, Soumalya; Chatterjee, Shovon; Bali, Somnath; Biswas, Tuyan; Sengupta, Sohini; Halder, Arnab
Abstract: Local environment dependent photoluminescence (PL) of cerium incorporated GO nanoparticles (GO−Ce NPs) is investigated by using fluorescence quenching study in presence of aromatic nitro compounds (ANCs) and fluoride ion. Presence of trivalent and tetravalent cerium ions at the different locations of the GO based nanoparticles interact with ANCs and fluoride ions in a different manner depending upon the accessibility and local polarity of the excited cerium (III) ions. Proposed system is found to be most sensitive towards ortho‐nitrophenol (quenching efficiency 70.5 %) with a high constant value of KD and KS, 8.7 × 10 4 and 7.0 × 10 4 respectively. Herein, the fluorescence quenching study of GO−Ce NPS reveals the different mode of interactions between the fluorophoric moieties and quenchers. Abstract : Highly photoluminescent cerium incorporated graphene oxide based nanoparticles (GO−Ce NPs) involves photoinduced reduction for converting tetravalent cerium ion to trivalent cerium ion. Interaction between the quenchers (aromatic nitro compounds or fluoride ion) with luminescent cerium depending upon local polarity and accessibility of the fluorophoric moiety restricts photoinduced reduction of tetravalent cerium by photoexcited GO and thereby the quenching of photoluminescence intensity occurs.